Multi-faceted roles of C1q/TNF-related proteins family in atherosclerosis - Guo, Shuren; Mao, Xiaohuan; Liu, Jun (Frontiers in Immunology, 2023)
C1q/TNF-related proteins (CTRPs) are involved in the modulation of the development and prognosis of atherosclerosis (AS). Here, we summarizes the pathophysiological roles of individual members of the CTRP superfamily in the development of AS. Currently, there is no specific efficacious treatment for AS-related diseases, therefore it is urgent to develop novel therapeutic strategies aiming to target key molecules involved in AS. Recent Findings Recently, mounting studies verified the critical roles of the CTRP family, including CTRP1-7, CTRP9 and CTRP11-15, in the development and progression of AS by influencing inflammatory response, modulating glucose and lipid metabolism, regulating endothelial functions and the proliferation of vascular smooth muscle cells (VSMCs).Conclusions CTRP family regulate different pathophysiology stages of AS. CTRP3, CTRP9, CTRP12, CTRP13 and CTRP15 play a clear protective role in AS, while CTRP5 and CTRP7 play a pro-atherosclerotic role in AS. The remarkable progress in our understanding of CTRPs' role in AS will provide an attractive therapeutic target for AS.